A new paradigm for temporal masking assessment: pilot study - Renata Filippini; Eliane Schochat (CoDAS)
PURPOSE: To determine the feasibility and applicability of a clinical backward masking test, focusing on the analysis of inter-stimuli interval, and not on the intensity thresholds as it has been traditionally done, thus proposing a new paradigm for temporal masking assessment.METHOD: The test consisted of the presentation of a target tone of 1.000 Hz followed by a broadband masking noise (950-1.050 Hz), with inter-stimuli interval of 0, 10, 20, 50 and 100 ms. The stimuli were presented monaurally to both ears, with intensity ratio between masker and target tone varying between -10, -20, -30 and -40 dB. Twenty undergraduate students, without hearing or auditory processing complaints, participated in this study.RESULTS: Regardless of the signal-to-noise ratio, we observed decrease of average performance according to the decrease of the interval between stimuli. We also observed the indication that little or no masking occurs at the 100 ms interval, suggesting this interval is unsuitable for temporal masking assessment. The average interval threshold was below 27 ms for all investigated intensities, and increased 9 ms with every increase of 10 dB at signal-to-noise ratio. The signal-to-noise ratios of -20 and -30 were the best ratios for the test application.CONCLUSION: The paradigm proposed in this pilot study proved to be feasible, easy to apply, and trustworthy, being compatible with other researches which are the foundation for the study of temporal masking. This theme deserves further studies, continuing the analysis initiated here.